SOSIALISASI WEBINAR PENGENALAN OLAHRAGA CRICKET BAGI GURU SMP PJOK DI KOTA BEKASI - Ahmad Muharib Fillah; Aridhotul Haqiyah; Hasan Basri (LPPM Universitas Islam 45 Bekasi, 2022)
Cricket is a sport that can be played by all ages and all groups of people, both teenagers and the general public. In general, sports have demands for achievement and there are even many competitions to sports in the village or even at a higher level. because it is a new sport in Indonesia, even though it is already a popular sport in the world. The target of this webinar activity is 30 junior high school physical education teachers in the city of Bekasi, West Java. This activity aims to introduce cricket to primary school PJOK teachers who will have the ability to form outstanding athletes. This webinar activity uses a training method that is divided into 3 stages (orientation, implementation, and evaluation), so that participants can be coordinated until the end of the event and there is an increase in teacher understanding regarding the material that has been delivered, namely history, equipment and cricket match rules.